Wildflower strips enhance pest regulation services in citrus orchards - Mockford, Alice; Urbaneja, Alberto; Ashbrook, Kate; Westbury, Duncan (Elsevier, 2024)
Contemporary approaches to agriculture must be reimaged to include ecological techniques that maximise ecosystem services, so that food can be produced sustainably whilst simultaneously meeting yield demands. Pest regulation services, harnessed through the conservation of natural enemies in the agri-environment are an economically important service degraded by conventional citrus production practices. For the first time, a sown wildflower strip composed of native forbs and tussock-forming grasses has been investigated for its influence on natural enemies and their pest regulation services in citrus orchards. A novel management strategy was applied, using the predicted generation times of Aonidiella aurantii Maskell (Hemiptera: Diaspididae), a key pest in citrus, to determine whether cutting the wildflower strips could force spill-over of natural enemies onto the adjacent crop, enhancing pest regulation services. Three treatments applied to orange orchard alleyways were compared: i) a control treatment, the standard orchard practice of regular cutting to 5 cm throughout the year, ii) a sown wildflower treatment managed with cutting once a year in February to a height of 10 cm (standard management wildflower treatment, SMWT), and iii) the same sown wildflower treatment but managed with two additional cuts in May and June (active management wildflower treatment, AMWT). Orange tree canopies were sampled for natural enemies, and pest regulation services were quantified using sentinel prey cards baited with Ephestia kuehniella eggs. Natural enemy richness was greatest in canopies with SMWT, supporting a greater relative abundance of primary parasitoids and lower relative abundances of antagonists (ants) compared to the control. This was associated with enhanced pest regulation services (depletion of sentinel prey from baited cards), especially during the early summer months, which coincides with a critical period to control A. aurantii and other key citrus pests. In contrast, AMWT did not enhance natural enemy richness, and pest regulation services were diminished. This study suggests that leaving wildflower strips uncut throughout the season, as in SMWT, may help to mitigate pest incidence through enhanced pest regulation services. Further studies are now required to determine how this would influence populations of target pests.